Interface Oral Health Science 2016: Innovative Research on Biosis-Abiosis Intelligent Interface - Sasaki, Keiichi; Suzuki, Osamu; Takahashi, Nobuhiro (Springer Nature, 2017)
Dentistry; Oral and Maxillofacial Surgery; Regenerative Medicine/Tissue Engineering